Typologies of Drivers Convicted of Driving under the Influence of Alcohol as Predictors of Alcohol Ignition Interlock Performance. Issue 1 (2nd January 2021) - Scherer, Michael; Nochajski, Thomas H.; Romano, Eduardo; Manning, Amy R.; Romosz, Ann; Tippetts, Scott; Taylor, Eileen; Voas, Robert; Paul, Roddia
ABSTRACT: Alcohol ignition interlock devices (IIDs) reduce rates of drinking and driving when installed on the vehicles of offenders. While the IID is installed on their vehicle, some drivers adapt their drinking behaviors, while others cannot. Heavy alcohol use and mental health concerns reduce treatment adherence in clinical settings, but it has not yet known how they pertain to behavioral adaptation to IIDs. This study focuses on identifying driver typologies as predictors of performance while on alcohol IIDs. The study utilizes the Managing Heavy Drinking study of drivers in New York state. Participants (N = 101; 59 males, 42 females) completed questionnaires assessing demographic information, drinking behaviors, driving history, and mental health measures. All participants had been convicted of a DUI, and installed an IID. Latent class analysis was used to establish typologies and predict lockout ratios. Four typologies emerged and drivers with elevations in mental health concerns had significantly worse lockout ratios than those in other classes. The current study may provide support for interventions designed to identify drivers with comorbid mental health concerns and tailor appropriate interventions to administer while the IID is installed with the aim of improving behavioral adaptation to the device.